2020
DOI: 10.1111/febs.15243
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of the N terminus of cardiac essential light chain promotes the super‐relaxed state of myosin and counteracts hypercontractility in hypertrophic cardiomyopathy mutant mice

Abstract: In this study, we focus on the molecular mechanisms associated with the A57G (Ala57‐to‐Gly57) mutation in myosin essential light chains (ELCs), found to cause hypertrophic cardiomyopathy (HCM) in humans and in mice. Specifically, we studied the effects of A57G on the super‐relaxed (SRX) state of myosin that may contribute to the hypercontractile cross‐bridge behavior and ultimately lead to pathological cardiac remodeling in transgenic Tg‐A57G mice. The disease model was compared to Tg‐WT mice, expressing the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…Recent studies of HCM-causing mutations in thick filament proteins, including β-cardiac myosin, myosin binding protein C, myosin regulatory light chain, and myosin essential light chain, have demonstrated that many of these mutations disrupt the autoinhibited super relaxed state of myosin, leading to the recruitment of more cross-bridges and thus to hypercontractility ( Spudich, 2015 ; McNamara et al, 2016 ; Alamo et al, 2017 ; Nag et al, 2017 ; Adhikari et al, 2019 ; Sitbon et al, 2020 ). It has been proposed that increased cross-bridge recruitment correlates with the hyperdynamic cardiac function seen in HCM ( Alamo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of HCM-causing mutations in thick filament proteins, including β-cardiac myosin, myosin binding protein C, myosin regulatory light chain, and myosin essential light chain, have demonstrated that many of these mutations disrupt the autoinhibited super relaxed state of myosin, leading to the recruitment of more cross-bridges and thus to hypercontractility ( Spudich, 2015 ; McNamara et al, 2016 ; Alamo et al, 2017 ; Nag et al, 2017 ; Adhikari et al, 2019 ; Sitbon et al, 2020 ). It has been proposed that increased cross-bridge recruitment correlates with the hyperdynamic cardiac function seen in HCM ( Alamo et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of the N-terminus of the ELC has been shown to increase myosin SRX (Fig. 4B) (Sitbon et al, 2020;Yadav et al, 2019a,b). Many of these variants are in close proximity to important IHM forming motifs in the IHM RLC-RLC interface, and may additionally interfere with RLC phosphorylation (Fig.…”
Section: Introductionmentioning
confidence: 92%
“…Based on that, a recent study has proven OM to have a positive therapeutic impact in patients with heart failure and reduced ejection fraction (Teerlink et al, 2020). N-terminally truncated ELC has been shown to lead to stabilization of myosin SRX (Sitbon et al, 2020). Constitutive cRLC phosphorylation in the MYL2 R58Q variant has been shown to increase DRX myosin (Yadav et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…A functionally important domain of the cardiac ELC is its 43-amino-acid-long N-terminal extension (N-ELC) shown by many to directly interact with the C-terminal region of actin ( Trayer et al, 1987 ; Milligan et al, 1990 ; Aydt et al, 2007 ; Kazmierczak et al, 2009 ; Wang et al, 2018 ). We previously reported that transgenic mice expressing the truncated N-ELC (Δ43 mice) display near-physiological cardiac remodeling with an increase in left ventricular (LV) wall thickness but no changes in cardiac morphology or function or in myofilament contraction/relaxation parameters are observed ( Sitbon et al, 2020 ). On the other hand, pathological hypertrophy due to hypertrophic cardiomyopathy (HCM) or restrictive cardiomyopathy (RCM) is characterized by interstitial fibrosis, myofilament disarray, reduced LV cavity, and impaired heart’s relaxation phase and can lead to diastolic dysfunction and sudden cardiac death ( Seidman and Seidman, 1998 ; Spirito et al, 2000 ; Arad et al, 2002 ; Ip et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this report, we focus on the A57G and E143K mutations in the ventricular ELC, the products of the mutated MYL3 gene that were shown by population studies to cause human HCM or RCM, respectively ( Lee et al, 2001 ; Olson et al, 2002 ; Caleshu et al, 2011 ). We previously reported that transgenic mice expressing the A57G ELC mutation (HCM-A57G model) exhibited characteristic HCM remodeling that included increased LV wall thickness, fibrosis, and diastolic abnormalities manifested by prolongation of isovolumetric relaxation time ( Sitbon et al, 2020 ). Skinned and intact papillary muscle (PM) experiments demonstrated increased Ca 2+ sensitivity of force, decreased maximal tension, and delayed Ca 2+ transients in HCM-A57G mice ( Kazmierczak et al, 2013 ; Sitbon et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%